Chronotype, circadian rhythms and mood. (August 2020) - Bauducco, Serena; Richardson, Cele; Gradisar, Michael
Highlights: Most studies measure morningness/eveningness preference rather than 'chronotype'. Few longitudinal studies exist, and show contrasting results for the direction of effect. Several studies point to sleep quality as potential mechanisms. Misalignment between circadian timing and preference might be a crucial risk for depression. Abstract : Growing evidence shows a link between mood and chronotype. The majority of studies measure chronotype as a preference for morning/evening activities, rather than actual sleep behaviour (i.e. midsleep) or biological markers of sleep timing (e.g. dim light melatonin onset). Most studies show an association between chronotype and mood and identify eveningness as a potential risk for depression, but the directionality is unclear. Some evidence shows a stronger association between misalignment with the biological clock and depressive symptoms. This review provides a snapshot of recent research on chronotype and unipolar depression. We conclude that future studies should strive to integrate different measures of chronotype. This will give a clearer picture of the association between early/late chronotype and mood, which will in turn better inform clinical practice.